Plasma and serum brain-derived neurotrophic factor (BDNF) levels and their association with neurocognition in at-risk mental state, first episode psychosis and chronic schizophrenia patients. (9th August 2019) - Heitz, Ulrike; Papmeyer, Martina; Studerus, Erich; Egloff, Laura; Ittig, Sarah; Andreou, Christina; Vogel, Tobias; Borgwardt, Stefan; Graf, Marc; Eckert, Anne; Riecher-Rössler, Anita
Abstract: Objectives: Brain-derived neurotrophic factor (BDNF) is involved in numerous cognitive processes. Since cognitive deficits are a core feature of psychotic disorders, the investigation of BDNF levels in psychosis and their correlation with cognition has received increased attention. However, there are no studies investigating BDNF levels in individuals with an at-risk mental state (ARMS) for psychosis. Hence, the aims of the present study were: (1) assessing peripheral BDNF levels across different (potential) stages of psychosis; (2) investigating their association with cognition. Methods: Plasma and serum BDNF levels and neuropsychological performance were assessed in 16 ARMS, six first-episode psychosis (FEP), and 11 chronic schizophrenia (CS) patients. Neuropsychological assessment covered intelligence, verbal memory, working memory, attention and executive functioning. Results: Both plasma and serum BDNF levels were highest in CS, intermediate in FEP and lowest in ARMS. Multiple regression analysis revealed a significant positive association of plasma BDNF levels with planning ability across all groups. Conclusions: The lower peripheral BDNF levels in ARMS compared to FEP and CS might point towards an important drop of this neurotrophin prior to the onset of frank psychosis. The associations of peripheral BDNF with planning-abilities match previous findings.